Activity of Colicin E3-Treated Ribosomes in Initiation and in Chain Elongation - Tai, Phang-Cheng (1974)
Colicin E3 (called E3 here) is shown to act on polysomal ribosomes as well as on free ribosomes. This treatment severely inhibits subsequent chain elongation, both on preformed polysomes completing their nascent chains and on ribosomes translating poly(U). Elevated Mg(++) concentration relieves this inhibition. However, elevated Mg(++) concentration does not relieve the inhibition of ribosomes initiating on natural messenger; hence damage by E3 appears to have an additional, specific effect on some stage in initiation. The effect of damage by E3 resembles that of streptomycin in several respects. This similarity suggests that the two agents may act on closely related sites on the ribosome.